Dark Triad and Men’s Objectification of Women among Male University Students: Mediating Role of Sexual Preoccupation - Mubeen, Beenish; Muhammad Zubair; Mujeeba Ashraf (Journal of Postgraduate Medical Institute, 2024)
Objective: The present study investigated the relationship between dark triad and sexual preoccupation with men’s objectification of women among male university students. Methodology: After the approval from Board of studies, this study was conducted as a cross-sectional correlational research. Through nonprobability purposive sampling, 200 male students of six different universities, with ages ranging from 18 to 25 years (M = 21.32, SD = 1.87), were enrolled in this study after taking informed consent. Assessment measures included personal information sheet, shorter dark triad scale, sexuality scale and men's objectification of women scale. Results: The research findings revealed that the Machiavellianism (P=.20**), Narcissism (P= .16*) and Psychopathy (P=.38**) showed positive association with the men’s objectification of women. However, sexual preoccupation depicted a negative relationship with psychopathy (P= -.18**) and men’s objectification of women (P= -.32**). Moreover, Machiavellianism, Narcissism and Psychopathy were shown to be the predictors of men’s objectification of women. Lastly, sexual preoccupation mediate the relationship of psychopathy and men’s objectification of women. Conclusion: These findings shed the light on complex interplay between dark personality traits and attitudes towards objectifying behavior, emphasizing the importance of understanding these dynamics in addressing issues related to objectification.